A simple electrogravimetric experimental setup to determine Cu in alloy samples for teaching purposes - Silva, João Pedro [UNESP]; Irikura, Kallyni [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Lima Gomes, Paulo Clairmont F. [UNESP] (Springer Nature, 2020)
Abstract: Electrogravimetry is a traditional analytical method for the determination of cations in aqueous solution, but the use of platinum as cathode and anode electrodes hinders its implementation in undergraduate chemistry courses with limited resources. This study proposes the replacement of expensive platinum electrodes by cheaper materials such as the dimensionally stable anode and Ni–Cr alloy as the cathode, which showed good performance in the determination of Cu by electrolysis at constant current (in galvanostatic mode). The proposed method achieved an electrogravimetric yield of 97.3 ± 0.9%, from a solution of CuSO4 during electrolysis carried out at 0.26 A for 60 min. The experimental setup was used to determine Cu in commercial scrap alloy waste samples containing Cu, Sn, Pb, and Zn, following a simple pretreatment employing ammonia solution. The Cu weight percentage obtained was 58.6 ± 0.5%, which was in agreement with a value of 59.4 ± 1.7% obtained using a comparative spectrophotometric method. Graphic abstract: [Figure not available: see fulltext.].
Keywords: Electroanalytical chemistry; Electrogravimetry; Instrumental method; Laboratory instruction; Quantitative analysis